Role of Health Education and Reproductive Health Education in Schools and Higher Education Institutions - Mouna, Hannaoui; N’djoli, Jacques; Maria, Hannaoui (CV. Literasi Indonesia, 2025)
Health education and sexual and reproductive health education are among the priority action plans of most countries, which have adopted policies focused on human rights. These countries aim to achieve the Sustainable Development Goals by 2030, to ensure access to health for all and to prepare future citizens for employment. The objective of this literature review is to assess the place of HE and SRH in educational curricula, from primary to higher education, to explore the strengths and weaknesses of the adopted didactic approaches and tools. This is a bibliographic study conducted using three scientific databases, Google Scholar, PubMed, and Science Direct, with the combination of keywords health education or reproductive health education, and curriculum or program or training or institute or health institute or nursing institute and approach and didactic. We obtained eleven articles. The target populations were students in primary and higher education (medical faculties and nursing institutes) and the teaching staff of primary and higher education institutions. The approaches identified in these studies were: traditional, biomedical, digital, interprofessional, and global or comprehensive approaches. A global consensus is required on how these competencies should be addressed, given the role they play in promoting the quality of life of individuals and ensuring a healthy environment, governed by a high level of health literacy.